A comparative study of users’ subjective feeling collection instruments - da Silva, Letícia Gabrielly Zacano; Guimarães, Patrícia Deud; Gomes, Luciana Oliveira de Souza; Neris, Vânia Paula de Almeida (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Although interaction with computational systems influences human emotions, knowing what emotion emerges is a rather complex task. Researchers from the Human-Computer Interaction field employ several different methods to measure altered emotions and collecting data about users’ subjective feeling is one of them. However, there is a lack of experimental studies that compare the different instruments used to evaluate these feelings. This paper carries out an investigation with four instruments – a set of emojis, the Self- Assessment Manikin, scroll sliders and Semantic Emotional Space – to find out which provides information about a subjective feeling that is closest to an emotion that has already been pre-classified by the literature for a given stimulus. The experiments involved 29 volunteers taking part in four experimental rounds. In each round, a volunteer watched a movie or part of a video clip and later randomly interacted with one of the instruments in a user interface. The results suggested that the scroll slider leads to a greater proximity to the pre-classified emotions.